Seminal Characteristics of Short-term Stored Spermatozoa of Indigenous Aseel Chicken in Bangladesh (Journal of Science and Technology Research, 2024)
The purpose of this study is to look at the seminal characteristics of short-term stored spermatozoa (at 4°C) from indigenous Aseel chickens in Bangladesh. The abdominal massage technique was utilized to collect semen from adult Aseel chickens at 3-day intervals and microscopically analyze the semen quality. The semen was then diluted with egg yolk-citrate (EYC) extender and stored at 4°C. They were then evaluated at various storage times, including Day 0 (0 hours), Day 1 (24 hours), Day 2 (48 hours), Day 3 (72 hours), Day 4 (96 hours), and Day 5 (120 hours). The findings of the study revealed that as storage time progressed, sperm motility, live spermatozoa, and the percentage of normal spermatozoa decreased. Total motility percentage significantly (P